2020
DOI: 10.1109/access.2020.3000457
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic and Secure SDN Framework for NoC-Based Many-Cores

Abstract: Recent exploration of Software-Defined Networking (SDN) for Many-Core Systems-on-Chip (MCSoCs) showed higher management flexibility and reduced physical complexity compared to other runtime communication management. In SDN, there is a software SDN Controller (control layer) that configures generic routers (data layer). The adoption of SDN makes the path establishment programmable and straightforward, according to different network policies, such as low power, QoS, fault-tolerance. It is also possible to change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…This demonstrates the power of our proposed system architecture interconnects over the conventional architecture interconnect. However, compared to the network structure in [20], their architecture enhanced the power consumption by 72.4%, while our proposed architecture produces an extra 6% enhancement to power consumption.…”
Section: B Simulation Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This demonstrates the power of our proposed system architecture interconnects over the conventional architecture interconnect. However, compared to the network structure in [20], their architecture enhanced the power consumption by 72.4%, while our proposed architecture produces an extra 6% enhancement to power consumption.…”
Section: B Simulation Results and Discussionmentioning
confidence: 88%
“…However, the objective of finding a general platform that suits any network for flexible chip control had a great deal in the research community. Researchers found that the concept of Software Defined Networks (SDN) can be applied to NoC [17], [18], [19], and [20]. The combination of these concepts produced a novel NoC management technology, which was called Software Defined Network on Chip (SDNoC) [21] and [22].…”
Section: Introductionmentioning
confidence: 99%
“…The M PE then configure the communicating task pair to use the new path. Further details about the Controller implementation are available at [7,25], including a distributed Controller implementation.…”
Section: B System Managementmentioning
confidence: 99%
“…The Controller accepts requests for SDN paths iff the M PE address is in M L, avoiding unauthorized path requests. The Controller rejects any packet whose address is not in M L [25].…”
Section: A Initializationmentioning
confidence: 99%
See 1 more Smart Citation